Fintech dan Bitcoin Modus Pencuci Uang Hasil Korupsi - Amalia Syauket; Jantarda Mauli Hutagalung; Muhammad Andi Prastio (KRTHA BHAYANGKARA, 2023)
The emergence of Fintech (financial technology) has shaken up the world of financial services. Thanks to technology, it has not only improved the quality of financial services but also their reach. However, Fintech is also vulnerable to abuse, such as money laundering crimes. This proves that the mode has morphed into an increasingly sophisticated direction as technology and information advances. Money laundering is an act of concealing or disguising the source of funds, so that funds that previously came from criminal acts, for example the proceeds of corruption, appear to come from legal economic activities. This qualitative research uses the latest secondary data relevant to the theme, aims to describe the phenomenon of the rise of money laundering resulting from corruption using the fintech & bitcoin mode. The results show that it is appropriate to use Fintech & Bitcoin as a means of laundering money resulting from corruption, either as a mode or from the money laundering stage, it is in accordance with the nature of Fintech & Bitcoin which is private or respects the confidentiality of the parties, which can result in criminals being able to hide or disguise the origin, sources of illegal funds in Fintech & Bitcoin. A series of new modus operandi that emphasize security, speed, and privacy from the advantages of Fintech & Bitcoin are chosen by perpetrators to disguise their tracks in cyberspace.